2002
DOI: 10.1117/12.485621
|View full text |Cite
|
Sign up to set email alerts
|

Application of the electro-mechanical impedance method for the identification of in-situ stress in structures

Abstract: In the beginning, the electro-mechanical (EM) impedance method for structural health monitoring was recognized as a means of structural in-situ stress monitoring and measurement. Consequently, theoretical analysis based on the EM impedance method as a tool for in-situ stress identification in structural members was presented. A dynamic impedance model derived from the Euler-Bernoulli beam theory was developed to investigate the influence of in-situ stress on the dynamic and electro-mechanical response of a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 12 publications
2
45
0
Order By: Relevance
“…These shifts are predominantly right-ward. Ong et al (2002) observed such similar trend in the numerical simulation of an axially loaded beam specimen. In their simulation, the beam specimen was axially loaded such that the surface bonded with the PZT transducer experienced a tensile effect.…”
Section: Influence Of Applied Load On Em Admittance Signaturesupporting
confidence: 74%
See 3 more Smart Citations
“…These shifts are predominantly right-ward. Ong et al (2002) observed such similar trend in the numerical simulation of an axially loaded beam specimen. In their simulation, the beam specimen was axially loaded such that the surface bonded with the PZT transducer experienced a tensile effect.…”
Section: Influence Of Applied Load On Em Admittance Signaturesupporting
confidence: 74%
“…Therefore, the observations of this study coincide with their study. Ong et al (2002) also noted that there is a shift in the natural frequencies of the smart system when the system undergoes in-situ stress. The shifts observed by them were proportionate to the magnitude of stress levels and are independent of the excitation frequencies.…”
Section: Influence Of Applied Load On Em Admittance Signaturementioning
confidence: 95%
See 2 more Smart Citations
“…Equation (1) shows that the output admittance signature is affected by both the structural and sensor dynamics, since the admittance is the response of the structure to the harmonic actuation of the piezoelectric transducer and the applied load will influence the response of the structure in the presence of mechanical impedance. The stress changes at a specific location on the structure will cause resonant frequency shift, and vibration mode change of the structure, which will be reflected in changes in the admittance signature [37,38].…”
Section: Introductionmentioning
confidence: 99%